Chordal rupture. I: aetiology and natural history. Issue 4 (October 1983) - Oliveira, D B; Dawkins, K D; Kay, P H; Paneth, M
Abstract : Between 1970 and 1981, 12% of patients undergoing mitral valve surgery were found to have chordal rupture. Spontaneous or primary rupture accounted for 74.6% of patients (primary group); in the remainder (secondary group) chordal rupture complicated chronic rheumatic valvular disease (8.9%), bacterial endocarditis on both normal (8.5%) and rheumatic valves (4.7%), ischaemic heart disease (2.3%), acute rheumatic fever (0.5%), and osteogenesis imperfecta (0.5%). Isolated posterior rupture was seen most frequently (54%), with anterior rupture in 36% and rupture of both mitral cusps in 10% of patients. A short symptomatic history of acute mitral regurgitation was rare, occurring in only 4% of patients in either the primary or secondary groups, suggesting that mitral regurgitation due to ruptured chordae is a progressive disease. In contrast to previous reports the clinical presentation did not help to differentiate the aetiology of the chordal rupture.